Roles of hepatic atypical protein kinase C hyperactivity and hyperinsulinemia in insulin‐resistant forms of obesity and type 2 diabetes mellitus - Mini P. Sajan; Barbara C. Hansen; Mildred Acevedo‐Duncan; Mark S. Kindy; Denise R. Cooper; Robert V. Farese (MedComm, 2021)
Abstract Diet‐induced obesity, the metabolic syndrome, type 2 diabetes (DIO/MetS/T2DM), and their adverse sequelae have reached pandemic levels. In mice, DIO/MetS/T2DM initiation involves diet‐dependent increases in lipids that activate hepatic atypical PKC (aPKC) and thereby increase lipogenic enzymes and proinflammatory cytokines. These or other hepatic aberrations, via adverse liver‐to‐muscle cross talk, rapidly impair postreceptor insulin signaling to glucose transport in muscle. The ensuing hyperinsulinemia further activates hepatic aPKC, which first blocks the ability of Akt to suppress gluconeogenic enzyme expression, and later impairs Akt activation, further increasing hepatic glucose production. Recent findings suggest that hepatic aPKC also increases a proteolytic enzyme that degrades insulin receptors. Fortunately, all hepatic aberrations and muscle impairments are prevented/reversed by inhibition or deficiency of hepatic aPKC. But, in the absence of treatment, hyperinsulinemia induces adverse events, some by using “spare receptors” to bypass receptor defects. Thus, in brain, hyperinsulinemia increases Aβ‐plaque precursors and Alzheimer risk; in kidney, hyperinsulinemia activates the renin–angiotensin–adrenal axis, thus increasing vasoconstriction, sodium retention, and cardiovascular risk; and in liver, hyperinsulinemia increases lipogenesis, obesity, hepatosteatosis, hyperlipidemia, and cardiovascular risk. In summary, increases in hepatic aPKC are critically required for development of DIO/MetS/T2DM and its adverse sequelae, and therapeutic approaches that limit hepatic aPKC may be particularly effective.